Nebenwirkungen neuer onkologischer Immuntherapien - Braun, G. S.; Kirschner, M.; Ruebben, A.; Wahl, R. U.; Amann, Kerstin Ute; Benesova, K.; Leipe, J. (Nephrologe, 2020)
Systemic treatment with immune checkpoint inhibitors (ICI) has revolutionized the treatment of hematological and oncological diseases in recent years. The mechanism of action hinges on enhancing the natural ability of the immune system to eliminate malignant cells. The most important substances in this arena include inhibitors of PD-1, PD-L1 and CTLA-4. As a consequence, the spectrum of treatment-associated adverse reactions is shifting away from classical cytotoxic effects (e.g. pancytopenia and polyneuropathy) towards novel entities of immune-mediated complex diseases. These so-called immune-related adverse events (irAEs) can involve any organ system and mimic known classical autoimmune conditions. Timely recognition of irAEs is the key for rapid initiation of a suitable treatment and is especially challenging in the clinical routine as it requires an intensive interdisciplinary management. Nephrologists are particularly confronted with this kind of problem due to the highly interdisciplinary nature of their work. This article summarizes the broad spectrum of currently known renal and more frequently occuring non-renal forms of irAEs and aims to prime the reader on diagnostic and therapeutic options.
CRIS-Team WoS Importer:2020-05-15